Arbuscular mycorrhizal fungi communities and glomalin mediate particulate and mineral-associated organic carbon formation in grassland patches - Deng Ao; Baorong Wang; Yubin Wang; Yuanjia Chen; Chao Liang; Shaoshan An (Communications Earth & Environment)
Abstract Arbuscular mycorrhizal fungi stimulate particulate and mineral-associated organic carbon formation and stabilization through hyphae residue, glomalin-related soil proteins gluing, and mycelium entangling. However, how grassland patches affect arbuscular mycorrhizal fungi- and glomalin-related soil proteins-mediated soil organic carbon formation and stabilization remains unclear. Here, we measured arbuscular mycorrhizal fungi diversity, glomalin-related soil proteins content, and plant- and microbial-derived carbon in particulate and mineral-associated organic carbon, through sampling of grassy, shrubby, degraded, and exposed patches. We found microbial-derived carbon dominates particulate and mineral-associated organic carbon formation. Decreased microbial- and plant-derived carbon in these fractions may relate to reduced arbuscular mycorrhizal fungi diversity in degraded patches, because fungal necromass carbon correlated more strongly with diversity decline than bacterial necromass. Grassland patches decrease arbuscular mycorrhizal fungi diversity and glomalin-related soil proteins content but stimulate their proportion, the cementation of glomalin-related soil proteins protect microbial-derived carbon from degradation, increasing its accumulation in both carbon fractions.